Genetic differentiation in Khaya Ivorensis A. Chev., a threaten tree of evergreen African rainforests - Bouka, Gaël U. D.; Doumenge, Charles; Ekue, Marius; Duminil, Jérôme; Florence, Jacques; Degen, Bernd; Loumeto, Jean Joël; McKey, Doyle; Hardy, Olivier J. (Springer, 2024)
Phylogeographic studies on widespread rainforest species from West and Central Africa often reveal genetic discontinuities. These discontinuities can originate from past barriers to gene flow resulting from long-lasting population fragmentation during glacial periods, according to the forest refuge hypothesis. This study 69 nuclear SNPs, 13 plastid SNPs, and 24 mitochondrial SNPs to characterized the distribution of genetic diversity in 377 individuals of the widespread tropical tree Khaya ivorensis, in western and central African evergreen forests. Two very well-differentiated nuclear genetic clusters (FST = 0.28) are located respectively in West and Central Africa. The gradual transition of allele frequencies between the clusters across a broad geographic area going from Cameroon to Nigeria accords with the recognition of a single species, although we show an incipient divergence that could eventually lead to the separation of two taxa. The two clusters have similar genetic diversity at nuclear SNPs. However, the cytoplasmic data revealed high haplotypic diversity and numerous endemic haplotypes in Central Africa, and only one widespread haplotype in West Africa, suggesting an ancient colonization of West Africa from Central Africa. The genetic diversity inside and outside putative forest refugia (Anhuf et al., Palaeogeogr Palaeoclimatol Palaeoecol 239:510–527, 2006) does not differ significantly in either genetic cluster. Hence, we cannot confirm that forest refugia played a particular role in the pattern of distribution of genetic diversity in K. ivorensis. Owing to the high haplotypic diversity of their populations, Central Africa, especially Gabon, constitutes a priority area for the conservation of the genetic diversity of K. ivorensis.